2021
DOI: 10.1007/s12088-021-00966-y
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Drug Resistance of Filamentous Fungi Isolated from the Fresh Raspberries

Abstract: Fungi are one of the most widely distributed microorganisms in the environment, including food such as fruits, vegetables and other crops, posing a potential threat to food safety and human health. The aim of this study was to determine the diversity, intensity and drug resistance of potentially pathogenic filamentous fungi isolated from the fresh raspberries (Rubus idaeus L.). A total of 50 strains belonging to genera Fusarium, Cladosporium, Alternaria, Penicillium, Mucor, Rhizopus, Aspergillus and Acremonium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Surprisingly, although raspberries are attacked by plant pathogenic fungi, that could also be potentially pathogenic for human consumers to a similar extent as strawberries, in spite of a thorough search of available databases, we were unable to find any study on mycobiota of raspberries. Two of the authors of the current study have already published a part of the results concerning raspberries shown in this study, with respect to the drug resistance of fungal isolates [20]. Overall, a high level of resistance was found which could reduce the treatment efficacy of potential fungal infections by transfer of resistance genes to fruit consumers.…”
Section: Introductionmentioning
confidence: 62%
“…Surprisingly, although raspberries are attacked by plant pathogenic fungi, that could also be potentially pathogenic for human consumers to a similar extent as strawberries, in spite of a thorough search of available databases, we were unable to find any study on mycobiota of raspberries. Two of the authors of the current study have already published a part of the results concerning raspberries shown in this study, with respect to the drug resistance of fungal isolates [20]. Overall, a high level of resistance was found which could reduce the treatment efficacy of potential fungal infections by transfer of resistance genes to fruit consumers.…”
Section: Introductionmentioning
confidence: 62%
“…It also encompasses addressing the potential risks they pose to the health of workers and visitors. Different strains belonging to Aspergillus, Penicillium, Rhizopus, Cladosporium, Paecilomyces, and Eurotium were isolated from libraries, archives, and museums and their health problems such as allergic infections, cutaneous inflammation, aspergillosis, otomycosis, respiratory infections, and endocarditis were investigated [18,46].…”
Section: Enzymatic Activitiesmentioning
confidence: 99%
“…The increase in AMR results in severe threats to human health, resulting in 700,000 deaths per annum, which is predicted to increase to 10 million per annum by the year 2050 . This catastrophe is manifested by fungi and bacteria. , The spread of infectious diseases poses severe risks to public health and the global economy . In addition, over the past 20 years, livestock farming has experienced the highest expansion in the agricultural sector, and more livestock farms are being established, which increases the need for antibiotic growth promoters in animals raised for food applications.…”
Section: Introductionmentioning
confidence: 99%